Response surface methodology to optimize self-flocculation harvesting of microalgae Desmodesmus sp.CHX1. Issue 17 (29th July 2022) - Zhang, Bangxi; Liu, Linhai; Lin, Xiaoai; Xu, Zhicheng; Luo, Wenhai; Luo, Longzao
ABSTRACT: This study aims to optimize the self-flocculation ability of microalgae Desmodesmus sp. CHX1 by the response surface methodology (RSM). Key parameters (i.e. pH, temperature and flocculation time) that significantly affected the Desmodesmus sp.CHX1 flocculation were determined. Results show that the flocculation efficiency of Desmodesmus sp.CHX1 increased in response to the prolonged settling time, particularly within the first 6 h, given the secretion of extracellular polymers. The RSM result suggested that both temperature and time exerted more significant effects on flocculation efficiency than solution pH. In specific, the maximum flocculation efficiency could reach 94.0% under the optimal conditions with the temperature, time and pH of 12.37°C, 6.96 h and 7.98, respectively. Validation experiments further indicated the reliability of the optimal parameter conditions. GRAPHICAL ABSTRACT: UF0001